Beyond borders, divisions and prejudices: Dimitrije Tucović on Albanians, Serbian-Albanian relations and Kosovo - Szczepański, Wojciech (Balcanica Posnaniensia. Acta et studia, 2009)
The article analyses the views and activities of Dimitrij Tucović (1881–1914), a Serbian socialist and intellectual from the early 20th century, who developed his reflections on the ‘Albanian question’. The background to these reflections are the events on the eve of and during the Balkan Wars (1912–1913), when Serbia incorporated Kosovo and Metohija into its borders and attempted to expand into northern Albania. The aim of the article is to present D. Tucović's political thought in relation to Serbian-Albanian relations and his alternative vision to Serbia's official policy. The source material is the text entitled Srbija i Arbanija (1914) and the journalism of D. Tucović's contemporary Serbian politicians and intellectuals. The article is based on a critical analysis of political discourse and comparative studies of the ideas of Balkan socialists and nationalists. D. Tucović was one of the few Serbian politicians who treated Albanians as a separate nation with the right to self-determination, recognising their claims to Kosovo and Metohija. He proposed solutions based on dialogue, respect for minority rights and the pursuit of a federation of democratic Balkan states. His criticism of the policy of conquest and his diagnosis of the inevitability of conflict over Kosovo remain relevant in contemporary reflections on Serbian-Albanian relations.